Farmers' Behavior Towards the Risks of Cabbage and Chicory Farming in Plaosan District, Magetan Regency, East Java - Sriyadi Sriyadi; Bambang Isnawan (Tropical Plantation Journal, 2026)
Vegetable horticultural goods like chicory and cabbage often face production and income risks. Rational farmers tend to be risk averse. Disparities in decision-making can result from individual differences in risk aversion. This study aims to (1) analyze the level of risk of costs, production, and income of cabbage and chicory farming; (2) analyze farmers' behavior towards the cost risk, production, and income of cabbage and chicory farming; and (3) analyze social factors that affect farmers' behavior on the risks of cabbage and chicory farming. A descriptive analytical method was used in the study. Observation and structured interviews with 100 farmers of cabbage and 100 farmers of chicory utilizing questionnaires were used to gather data. The findings indicate that growing cabbage is riskier than growing chicory. Regarding both commodities, the majority of farmers behave in a risk-averse manner. Risk aversion falls with better education, more years of agricultural experience, larger households, and higher farm revenue, but rises with larger acreage, older age, and more frequent crop failure. In general, farmers who grow cabbage are less willing to take risks than those who grow chicory. In order to lower farming hazards and increase revenue stability, extension programs are crucial for enhancing farmers' knowledge of the best times to grow chicory and cabbage.